A novel quantitative PCR assay for the detection of Streptococcus pneumoniae using the competence regulator gene target comX. Issue 2 (1st February 2016) - Habets, Marrit N.; Cremers, Amelieke J. H.; Bos, Martine P.; Savelkoul, Paul; Eleveld, Marc J.; Meis, Jacques F.; Hermans, Peter W. M.; Melchers, Willem J.; de Jonge, Marien I.; Diavatopoulos, Dimitri A.
Abstract : Streptococcus pneumoniae is responsible for an estimated 1.6 million deaths worldwide every year. While rapid detection and timely treatment with appropriate antibiotics is preferred, this is often difficult due to the amount of time that detection with blood cultures takes. In this study, a novel quantitative PCR assay for the detection of Streptococcus pneumoniae was developed. To identify novel targets, we analysed the pneumococcal genome for unique, repetitive DNA sequences. This approach identified comX, which is conserved and present in duplicate copies in Streptococcus pneumoniae but not in other bacterial species. Comparison with lytA, the current 'gold standard' for detection by quantitative PCR, demonstrated an analytic specificity of 100 % for both assays on a panel of 10 pneumococcal and 18 non-pneumococcal isolates, but a reduction of 3.5 quantitation cycle values ( ± 0.23 SEM), resulting in an increased analytical detection rate of comX. We validated our assay on DNA extracted from the serum of 30 bacteraemic patients who were blood culture positive for Streptococcus pneumoniae and 51 serum samples that were culture positive for other bacteria. This resulted in a similar clinical sensitivity between the comX and lytA assays (47 %) and in a diagnostic specificity of 98.2 and 100 % for the lytA and comX assays, respectively. In conclusion, we have developed a novel quantitative PCR assay with increased analytical sensitivity for the detection of Streptococcus pneumoniae, which may be used to develop a rapid bedside test for the direct detection of Streptococcus pneumoniae in clinical specimens.